Political Parties and the Concept of Power : A Theoretical Framework - Rye, Danny; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
An original investigation of the nature of the forces that make members and representatives both loyal and beneficial to a contemporary political party, this book combines theoretical reflection with interview and archive material to provide a unique perspective on power, arguing that it is more complex and nuanced than is frequently assumed.
Keywords: Science; Science, general